Antistatic chenille floor mat and production process

By grafting unsaturated groups and photopolymerization modification on the surface of the polyester base cloth, and combining the use of modified carbon nanotubes, modified polyester filaments were prepared, which solved the problem of Chenille floor mats being prone to accumulation of static electricity and adsorbed dust bacteria, achieving good anti-static and anti-bacterial properties, and maintaining the anti-static properties for long-term use.

CN119531129AInactive Publication Date: 2025-02-28JIANGSU DUOLAIYUN TEXTILE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411796489.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-02-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing Chenille floor mats are prone to accumulation of static electricity, causing static damage, and static electricity will also absorb dust and bacteria, making it difficult to clean and breed bacteria.

Method used

By grafting unsaturated groups on the surface of the polyester base cloth and modifying the polyester base cloth through photopolymerization, the surface is covered with a film containing quaternary ammonium-sulfonic acid amphoteric groups. Combined with the use of modified carbon nanotubes, modified polyester filaments are prepared for making anti-static Chenilli floor mats.

Benefits of technology

The good antistatic and antibacterial properties of the modified Chenille floor mat are achieved. At the same time, due to the existence of the film, the floor mat still maintains good antistatic properties during long-term use and has good anti-water washing performance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of floor mats, in particular to an anti-static chenille floor mat and a production process, unsaturated groups are grafted on the surface of polyester base cloth, and the polyester base cloth is modified through photopolymerization, so that the modified polyester base cloth has good anti-static performance and antibacterial performance, and has good washing resistance; the anti-static performance of the anti-static chenille ground mat in the long-term use process is further guaranteed, the chenille yarn raw material filaments are modified, modified carbon nanotubes are added in the polyester raw material preparation process, the modified polyester filaments are prepared, and the chenille yarn prepared from the modified polyester filaments has good anti-static performance and antibacterial performance, so that the anti-static performance of the anti-static chenille ground mat is improved, and the anti-static performance of the anti-static chenille ground mat is improved. Therefore, the antistatic performance and the antibacterial performance of the chenille floor mat in the long-term use process are guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of floor mats, and in particular to an antistatic chenille floor mat and a production process. Background Art

[0002] Chenille yarn is a yarn made of short fibers or filaments of different fineness and strength twisted together. It is widely used in various fields, such as chenille mats, because of its plump down, soft touch, thick fabric and light texture. However, due to the special structure of chenille yarn, chenille mats are prone to accumulate static electricity, causing static electricity damage. The accumulated static electricity will also absorb dust and bacteria, making it difficult to clean the mats and breeding bacteria. Summary of the invention

[0003] The purpose of the present invention is to provide an antistatic chenille mat and a production process, which solves the problem of poor antistatic performance of existing chenille mats, and the antistatic performance is long-lasting and stable, and the chenille mat also has a certain antibacterial ability.

[0004] The purpose of the present invention can be achieved by the following technical solution: An antistatic chenille mat is made by the following steps: Step S1: adding modified polyester to a melt spinning machine, melt spinning, and obtaining modified polyester filaments, and passing through a chenille spinning machine, using two polyester filaments as core yarns, three polyester filaments and two modified polyester filaments as decorative yarns, the polyester filaments and the modified polyester filaments are arranged alternately, and the decorative yarns are clamped between the two core yarns and twisted in a spiral shape to obtain modified chenille yarns; Step S2: feeding the modified chenille yarn and the modified polyester base fabric into a tufting loom, and then dyeing, finishing, repairing, and backing to obtain a chenille waterproof floor mat; The modified polyester base fabric is prepared by the following steps: Step A1: Mix a polyester base fabric and a sodium hydroxide aqueous solution, add a hexadecyl trimethyl ammonium bromide solution at a temperature of 80-90° C., soak and react for 1-1.5 hours, and dry to obtain an activated polyester base fabric; mix the activated polyester base fabric, methacrylic anhydride and deionized water, adjust the pH value to 7.5, and soak and react for 24 hours at a temperature of 5° C. to obtain a grafted polyester base fabric; The mass concentration of the sodium hydroxide aqueous solution is 1g / L, the hexadecyltrimethylammonium bromide solution is 2.5g / L, the dosage ratio of the polyester base fabric, the sodium hydroxide aqueous solution and the hexadecyltrimethylammonium bromide is 10-12g: 100-120mL: 40-50mL, and the dosage ratio of the activated polyester base fabric and methacrylic anhydride is 10-12g: 0.08-0.1mol; During the reaction, under alkaline conditions, the polyester base fabric is hydrolyzed under the action of the hexadecyltrimethylammonium bromide solution, so that active hydroxyl groups appear on the surface of the polyester base fabric to obtain an activated polyester base fabric. The hydroxyl groups in the activated polyester base fabric react with the anhydride groups in methacrylic anhydride to form ester groups, and unsaturated double bonds are introduced to obtain a grafted polyester base fabric. Step A2: methacrylic acid, p-toluenesulfonic acid and trimethyl-1,3-propylenediamine are mixed, and the mixture is reacted for 3-4 hours under nitrogen protection, at a stirring rate of 240-300 rpm and a temperature of 100° C. to obtain intermediate 1; intermediate 1, sodium 3-chloro-2-hydroxypropanesulfonate and anhydrous ethanol are mixed, the pH is adjusted to 7.5, and the mixture is reacted for 6-8 hours under a stirring rate of 240-300 rpm and a temperature of 80° C. to obtain intermediate 2; The ratio of methacrylic acid, p-toluenesulfonic acid and trimethyl-1,3-propylenediamine is 0.1-0.12 mol: 0.5 g: 0.1-0.12 mol, and the ratio of intermediate 1 and sodium 3-chloro-2-hydroxypropanesulfonate is 0.1-0.12 mol: 0.12-0.14 mol; During the reaction, under the action of p-toluenesulfonic acid, the carboxyl group in methacrylic acid reacts with the primary amine group in trimethyl-1,3-propylenediamine to form an amide group to obtain intermediate 1, and the tertiary amine group in intermediate 1 reacts with the chlorine atom in sodium 3-chloro-2-hydroxypropanesulfonate to form a quaternary ammonium salt structure to obtain intermediate 2; Step A3: Mix the intermediate 2, methacrylate and deionized water, immerse the grafted polyester base fabric in it, add 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone, and immerse and react for 15-20 minutes under nitrogen protection and 365nm ultraviolet irradiation at room temperature to obtain a modified polyester base fabric; The ratio of intermediate 2, methacrylate, deionized water and 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone is 0.1 mol: 0.1-0.12 mol: 150-200 mL: 2-3 g; During the reaction, under the action of the photoinitiator 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone, the double bonds in the intermediate 2, methacrylate and grafted polyester base fabric are photopolymerized to obtain a modified polyester base fabric; The modified polyester is prepared by the following steps: Step B1: Mix carbon nanotubes, nitric acid solution and sulfuric acid solution, and react for 1 hour at a stirring rate of 200-240rpm and a temperature of 110°C to obtain activated carbon nanotubes; mix sodium alginate, silver nitrate solution and deionized water, and stir and add glucose solution at a stirring rate of 200-240rpm and a temperature of 80°C, and react for 2 hours; then add activated carbon nanotubes and continue to react for 4-6 hours to obtain doped carbon nanotubes; The mass fraction of the nitric acid solution is 65%, the mass fraction of the sulfuric acid solution is 95%, the amount ratio of the carbon nanotubes, the nitric acid solution and the sulfuric acid solution is 0.5-1g:10-12mL:30-36mL, the molar concentration of the silver nitrate solution is 0.1mol / L, the mass fraction of the glucose solution is 5%, and the amount ratio of the sodium alginate, the silver nitrate solution, the glucose solution and the activated carbon nanotubes is 100mL:10-12mL:45-50mL:0.2g; During the reaction, the carbon nanotubes are activated under the action of nitric acid solution and sulfuric acid solution, so that the carbon nanotubes have carboxyl groups on their surfaces, thereby obtaining activated carbon nanotubes; the silver ions in the silver nitrate solution are reduced under the action of sodium alginate and glucose solution, and activated carbon nanotubes are added at the same time, so that silver is assembled in the carbon nanotubes, thereby obtaining doped carbon nanotubes; Step B2: Mix the doped carbon nanotubes, methanol and deionized water, stir and add 3-(methacryloyloxy)propyltrimethoxysilane at a stirring rate of 300-360 rpm and a temperature of 50°C, adjust the pH to 3.5, and react for 4-6 hours to obtain grafted carbon nanotubes. Mix lactide and N,N-dimethylformamide, stir and add grafted carbon nanotubes and stannous octoate at a stirring rate of 300-360 rpm and a temperature of 120°C, and react for 6-8 hours to obtain wrapped carbon nanotubes; The ratio of doped carbon nanotubes to 3-(methacryloyloxy)propyltrimethoxysilane is 1.8-2.2 g: 0.1-0.12 mol, and the ratio of lactide, grafted carbon nanotubes and stannous octoate is 0.005-0.008 mol: 1.8-2.2 g: 0.1 g; During the reaction, the siloxy groups in 3-(methacryloyloxy)propyltrimethoxysilane are hydrolyzed under acidic conditions and grafted onto the doped carbon nanotubes to obtain grafted carbon nanotubes. Lactide then undergoes ring-opening polymerization under the action of stannous octoate and is wrapped around the grafted carbon nanotubes to obtain wrapped carbon nanotubes. Step B3: Mix the wrapped carbon nanotubes, dimethyl terephthalate and ethylene glycol, stir at a stirring rate of 200-240 rpm and a temperature of 200° C., add n-butyl titanate, react for 1-2 hours, then heat to 250° C. and control the vacuum degree to -0.099 MPa, react for 6 hours, and obtain a modified polyester; The ratio of wrapped carbon nanotubes, dimethyl terephthalate, ethylene glycol and n-butyl titanate is 4-5 g: 0.5-0.55 mol: 0.8-1 mol: 0.2-0.25 g; During the reaction, under the action of n-butyl titanate, the ester groups on the surface of the carbon nanotubes and the ester groups of dimethyl terephthalate undergo ester exchange reaction with the hydroxyl groups in ethylene glycol to obtain modified polyester; Beneficial effects of the invention: The invention relates to an antistatic chenille mat and a production process. Unsaturated groups are grafted onto the surface of a polyester base fabric and the polyester base fabric is modified by photopolymerization, so that the surface of the polyester base fabric is covered with a film containing quaternary ammonium-sulfonic acid amphoteric groups. Due to the antistatic properties of the amphoteric groups, the modified polyester base fabric has good antistatic properties, and the presence of the quaternary ammonium groups also gives the modified polyester base fabric certain antibacterial properties. At the same time, since the film is obtained by direct reaction of intermediate 2 and methacrylate with unsaturated groups on the surface of the polyester base fabric, the film has good water washing resistance, thereby ensuring the antistatic performance of the antistatic chenille mat during long-term use; by modifying the chenille yarn raw material filaments, adding the modified filaments in the preparation process of the polyester raw material Carbon nanotubes are used to prepare modified polyester filaments. Silver is assembled in the carbon nanotubes through the modification of the carbon nanotubes, which have good electrical conductivity and certain antibacterial ability. The surface of the carbon nanotubes is modified by 3-(methacryloyloxy)propyltrimethoxysilane and wrapped with lactide, so that the carbon nanotubes can participate in the reaction process of preparing polyester by ester exchange between dimethyl terephthalate and ethylene glycol, thereby improving the dispersion of the wrapped carbon nanotubes in the polyester and better forming a conductive path in the polyester, so that the modified polyester filaments have conductive ability, and the carbon nanotubes are connected to the polyester by chemical bonds, which reduces the shedding of the carbon nanotubes during use, so that the chenille yarn has good antistatic and antibacterial properties, thereby ensuring the antistatic and antibacterial properties of the chenille mat during long-term use. DETAILED DESCRIPTION

[0005] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1

[0006] An antistatic chenille floor mat is made by the following steps: Step S1: adding the modified polyester to a melt spinning machine, melt spinning, and obtaining modified polyester filaments, and passing through a chenille spinning machine, using two commercially available Huilihua polyester filaments as core yarns, three commercially available Huilihua polyester filaments and two modified polyester filaments as decorative yarns, the polyester filaments and the modified polyester filaments are arranged alternately, and the decorative yarns are clamped between the two core yarns and twisted in a spiral shape to obtain modified chenille yarns; Step S2: feeding the modified chenille yarn and the modified polyester base fabric into a tufting loom, and then dyeing, finishing, repairing, and backing to obtain a chenille waterproof floor mat; The modified polyester base fabric is prepared by the following steps: Step A1: Mix the commercially available Xinfudi polyester base fabric and a sodium hydroxide aqueous solution, add a hexadecyl trimethyl ammonium bromide solution at a temperature of 80°C, soak and react for 1.5 hours, and dry to obtain an activated polyester base fabric; mix the activated polyester base fabric, methacrylic anhydride and deionized water, adjust the pH value to 7.5, soak and react for 24 hours at a temperature of 5°C to obtain a grafted polyester base fabric; The mass concentration of the sodium hydroxide aqueous solution is 1g / L, the hexadecyltrimethylammonium bromide solution is 2.5g / L, the amount ratio of the polyester base fabric, the sodium hydroxide aqueous solution and the hexadecyltrimethylammonium bromide is 10g:100mL:40mL, and the amount ratio of the activated polyester base fabric and methacrylic anhydride is 10g:0.08mol; Step A2: methacrylic acid, p-toluenesulfonic acid and trimethyl-1,3-propylenediamine were mixed, and the mixture was reacted for 4 hours under nitrogen protection, at a stirring rate of 240 rpm and a temperature of 100° C. to obtain intermediate 1; intermediate 1, sodium 3-chloro-2-hydroxypropanesulfonate and anhydrous ethanol were mixed, the pH was adjusted to 7.5, and the mixture was reacted for 8 hours under a stirring rate of 240 rpm and a temperature of 80° C. to obtain intermediate 2; The ratio of methacrylic acid, p-toluenesulfonic acid and trimethyl-1,3-propylenediamine is 0.1 mol: 0.5 g: 0.1 mol, and the ratio of intermediate 1 and sodium 3-chloro-2-hydroxypropanesulfonate is 0.1 mol: 0.12 mol; Step A3: Mix the intermediate 2, methacrylate and deionized water, immerse the grafted polyester base fabric in it, add 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone, and immerse and react for 15 minutes under nitrogen protection and 365nm ultraviolet irradiation at room temperature to obtain a modified polyester base fabric; The amount ratio of intermediate 2, methacrylate, deionized water and 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone is 0.1 mol: 0.1 mol: 150 mL: 2 g; The modified polyester is prepared by the following steps: Step B1: Mix commercially available Liso 20 μm carbon nanotubes, nitric acid solution and sulfuric acid solution, react for 1 hour at a stirring rate of 200 rpm and a temperature of 110°C to obtain activated carbon nanotubes, mix sodium alginate, silver nitrate solution and deionized water, stir and add glucose solution at a stirring rate of 200 rpm and a temperature of 80°C, react for 2 hours, then add activated carbon nanotubes, and continue to react for 6 hours to obtain doped carbon nanotubes; The mass fraction of nitric acid solution is 65%, the mass fraction of sulfuric acid solution is 95%, the amount ratio of carbon nanotubes, nitric acid solution and sulfuric acid solution is 0.5g:10mL:30mL, the molar concentration of silver nitrate solution is 0.1mol / L, the mass fraction of glucose solution is 5%, and the amount ratio of sodium alginate, silver nitrate solution, glucose solution and activated carbon nanotubes is 100mL:10mL:45mL:0.2g; Step B2: Mix the doped carbon nanotubes, methanol and deionized water, stir and add 3-(methacryloyloxy)propyltrimethoxysilane at a stirring rate of 300 rpm and a temperature of 50°C, adjust the pH to 3.5, and react for 6 hours to obtain grafted carbon nanotubes. Mix lactide and N,N-dimethylformamide, stir and add grafted carbon nanotubes and stannous octoate at a stirring rate of 300 rpm and a temperature of 120°C, and react for 8 hours to obtain wrapped carbon nanotubes; The ratio of doped carbon nanotubes to 3-(methacryloyloxy)propyltrimethoxysilane was 1.8 g:0.1 mol, and the ratio of lactide, grafted carbon nanotubes and stannous octoate was 0.005 mol:1.8 g:0.1 g; Step B3: Mix the wrapped carbon nanotubes, dimethyl terephthalate and ethylene glycol, stir at a stirring rate of 200 rpm and a temperature of 200° C., add n-butyl titanate, react for 2 h, then heat to 250° C. and control the vacuum degree to -0.099 MPa, react for 6 h, and obtain a modified polyester; The amount ratio of wrapped carbon nanotubes, dimethyl terephthalate, ethylene glycol and n-butyl titanate is 4g:0.5mol:0.8mol:0.2g. Example 2

[0007] An antistatic chenille floor mat is made by the following steps: Step S1: adding the modified polyester to a melt spinning machine, melt spinning, and obtaining modified polyester filaments, and passing through a chenille spinning machine, using two commercially available Huilihua polyester filaments as core yarns, three commercially available Huilihua polyester filaments and two modified polyester filaments as decorative yarns, the polyester filaments and the modified polyester filaments are arranged alternately, and the decorative yarns are clamped between the two core yarns and twisted in a spiral shape to obtain modified chenille yarns; Step S2: feeding the modified chenille yarn and the modified polyester base fabric into a tufting loom, and then dyeing, finishing, repairing, and backing to obtain a chenille waterproof floor mat; The modified polyester base fabric is prepared by the following steps: Step A1: Mix the commercially available Xinfudi polyester base fabric and a sodium hydroxide aqueous solution, add a hexadecyl trimethyl ammonium bromide solution at a temperature of 80°C, soak and react for 1 hour, and dry to obtain an activated polyester base fabric; mix the activated polyester base fabric, methacrylic anhydride and deionized water, adjust the pH value to 7.5, soak and react for 24 hours at a temperature of 5°C to obtain a grafted polyester base fabric; The mass concentration of the sodium hydroxide aqueous solution is 1g / L, the mass concentration of the hexadecyltrimethylammonium bromide solution is 2.5g / L, the amount ratio of the polyester base fabric, the sodium hydroxide aqueous solution and the hexadecyltrimethylammonium bromide is 12g:100mL:50mL, and the amount ratio of the activated polyester base fabric and methacrylic anhydride is 12g:0.08mol; Step A2: methacrylic acid, p-toluenesulfonic acid and trimethyl-1,3-propylenediamine were mixed, and the mixture was reacted for 3 h under nitrogen protection, at a stirring rate of 300 rpm and a temperature of 100° C. to obtain intermediate 1; intermediate 1, sodium 3-chloro-2-hydroxypropanesulfonate and anhydrous ethanol were mixed, the pH was adjusted to 7.5, and the mixture was reacted for 6 h under a stirring rate of 300 rpm and a temperature of 80° C. to obtain intermediate 2; The ratio of methacrylic acid, p-toluenesulfonic acid and trimethyl-1,3-propylenediamine is 0.12 mol: 0.5 g: 0.1 mol, and the ratio of intermediate 1 and sodium 3-chloro-2-hydroxypropanesulfonate is 0.12 mol: 0.12 mol; Step A3: Mix the intermediate 2, methacrylate and deionized water, immerse the grafted polyester base fabric in it, add 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone, and immerse and react for 20 minutes under nitrogen protection and 365nm ultraviolet irradiation at room temperature to obtain a modified polyester base fabric; The ratio of intermediate 2, methacrylate, deionized water and 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone is 0.1 mol: 0.12 mol: 150 mL: 2 g; The modified polyester is prepared by the following steps: Step B1: Mix commercially available Liso 20 μm carbon nanotubes, nitric acid solution and sulfuric acid solution, and react for 1 hour at a stirring rate of 240 rpm and a temperature of 110°C to obtain activated carbon nanotubes; mix sodium alginate, silver nitrate solution and deionized water, and stir and add glucose solution at a stirring rate of 240 rpm and a temperature of 80°C, and react for 2 hours; then add activated carbon nanotubes and continue to react for 4 hours to obtain doped carbon nanotubes; The mass fraction of nitric acid solution is 65%, the mass fraction of sulfuric acid solution is 95%, the amount ratio of carbon nanotubes, nitric acid solution and sulfuric acid solution is 0.5g:10mL:30mL, the molar concentration of silver nitrate solution is 0.1mol / L, the mass fraction of glucose solution is 5%, and the amount ratio of sodium alginate, silver nitrate solution, glucose solution and activated carbon nanotubes is 100mL:12mL:45mL:0.2g; Step B2: Mix the doped carbon nanotubes, methanol and deionized water, stir and add 3-(methacryloyloxy)propyltrimethoxysilane at a stirring rate of 360 rpm and a temperature of 50°C, adjust the pH to 3.5, and react for 4-6 hours to obtain grafted carbon nanotubes. Mix lactide and N,N-dimethylformamide, stir and add grafted carbon nanotubes and stannous octoate at a stirring rate of 360 rpm and a temperature of 120°C, and react for 6 hours to obtain wrapped carbon nanotubes. The ratio of doped carbon nanotubes to 3-(methacryloyloxy)propyltrimethoxysilane was 2.2 g:0.1 mol, and the ratio of lactide, grafted carbon nanotubes and stannous octoate was 0.008 mol:1.8 g:0.1 g; Step B3: mixing the wrapped carbon nanotubes, dimethyl terephthalate and ethylene glycol, stirring at a rate of 240 rpm and a temperature of 200° C., adding n-butyl titanate, reacting for 1 h, then heating to 250° C. and controlling the vacuum degree to -0.099 MPa, reacting for 6 h, to obtain a modified polyester; The amount ratio of wrapped carbon nanotubes, dimethyl terephthalate, ethylene glycol and n-butyl titanate is 5g:0.55mol:0.8mol:0.2g. Example 3

[0008] An antistatic chenille floor mat is made by the following steps: Step S1: adding the modified polyester to a melt spinning machine, melt spinning, and obtaining modified polyester filaments, and passing through a chenille spinning machine, using two commercially available Huilihua polyester filaments as core yarns, three commercially available Huilihua polyester filaments and two modified polyester filaments as decorative yarns, the polyester filaments and the modified polyester filaments are arranged alternately, and the decorative yarns are clamped between the two core yarns and twisted in a spiral shape to obtain modified chenille yarns; Step S2: feeding the modified chenille yarn and the modified polyester base fabric into a tufting loom, and then dyeing, finishing, repairing, and backing to obtain a chenille waterproof floor mat; The modified polyester base fabric is prepared by the following steps: Step A1: Mix the commercially available Xinfudi polyester base fabric and a sodium hydroxide aqueous solution, add a hexadecyltrimethylammonium bromide solution at a temperature of 90°C, soak and react for 1.5 hours, and dry to obtain an activated polyester base fabric; mix the activated polyester base fabric, methacrylic anhydride and deionized water, adjust the pH value to 7.5, and soak and react for 24 hours at a temperature of 5°C to obtain a grafted polyester base fabric; The mass concentration of the sodium hydroxide aqueous solution is 1g / L, the mass concentration of the hexadecyltrimethylammonium bromide solution is 2.5g / L, the amount ratio of the polyester base fabric, the sodium hydroxide aqueous solution and the hexadecyltrimethylammonium bromide is 12g:120mL:50mL, and the amount ratio of the activated polyester base fabric and methacrylic anhydride is 12g:0.1mol; Step A2: methacrylic acid, p-toluenesulfonic acid and trimethyl-1,3-propylenediamine were mixed, and the mixture was reacted for 4 hours under nitrogen protection, at a stirring rate of 300 rpm and a temperature of 100° C. to obtain intermediate 1; intermediate 1, sodium 3-chloro-2-hydroxypropanesulfonate and anhydrous ethanol were mixed, the pH was adjusted to 7.5, and the mixture was reacted for 8 hours under a stirring rate of 300 rpm and a temperature of 80° C. to obtain intermediate 2; The ratio of methacrylic acid, p-toluenesulfonic acid and trimethyl-1,3-propylenediamine is 0.12 mol: 0.5 g: 0.12 mol, and the ratio of intermediate 1 and sodium 3-chloro-2-hydroxypropanesulfonate is 0.12 mol: 0.14 mol; Step A3: Mix the intermediate 2, methacrylate and deionized water, immerse the grafted polyester base fabric in it, add 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone, and immerse and react for 20 minutes under nitrogen protection and 365nm ultraviolet irradiation at room temperature to obtain a modified polyester base fabric; The amount ratio of intermediate 2, methacrylate, deionized water and 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone is 0.1 mol: 0.12 mol: 200 mL: 3 g; The modified polyester is prepared by the following steps: Step B1: Mix commercially available Liso 20 μm carbon nanotubes, nitric acid solution and sulfuric acid solution, and react for 1 h at a stirring rate of 240 rpm and a temperature of 110°C to obtain activated carbon nanotubes; mix sodium alginate, silver nitrate solution and deionized water, and stir and add glucose solution at a stirring rate of 240 rpm and a temperature of 80°C, and react for 2 h; then add activated carbon nanotubes and continue to react for 6 h to obtain doped carbon nanotubes; The mass fraction of nitric acid solution is 65%, the mass fraction of sulfuric acid solution is 95%, the amount ratio of carbon nanotubes, nitric acid solution and sulfuric acid solution is 1g:12mL:36mL, the molar concentration of silver nitrate solution is 0.1mol / L, the mass fraction of glucose solution is 5%, and the amount ratio of sodium alginate, silver nitrate solution, glucose solution and activated carbon nanotubes is 100mL:12mL:50mL:0.2g; Step B2: Mix the doped carbon nanotubes, methanol and deionized water, stir and add 3-(methacryloyloxy)propyltrimethoxysilane at a stirring rate of 360 rpm and a temperature of 50°C, adjust the pH to 3.5, and react for 6 hours to obtain grafted carbon nanotubes. Mix lactide and N,N-dimethylformamide, stir and add grafted carbon nanotubes and stannous octoate at a stirring rate of 360 rpm and a temperature of 120°C, and react for 8 hours to obtain wrapped carbon nanotubes. The ratio of doped carbon nanotubes to 3-(methacryloyloxy)propyltrimethoxysilane was 2.2 g:0.12 mol, and the ratio of lactide, grafted carbon nanotubes and stannous octoate was 0.008 mol:2.2 g:0.1 g; Step B3: mixing the wrapped carbon nanotubes, dimethyl terephthalate and ethylene glycol, stirring at a rate of 240 rpm and a temperature of 200° C., adding n-butyl titanate, reacting for 2 h, then heating to 250° C. and controlling the vacuum degree to -0.099 MPa, reacting for 6 h, to obtain a modified polyester; The amount ratio of wrapped carbon nanotubes, dimethyl terephthalate, ethylene glycol and n-butyl titanate is 5g:0.55mol:1mol:0.25g.

[0009] Comparative Example 1 Compared with Example 3, this comparative example replaces the grafted polyester base fabric in the preparation process of the modified polyester base fabric in Example 3 with the commercially available Xinfudi polyester base fabric, and the other steps are the same.

[0010] Comparative Example 2 Compared with Example 3, this comparative example replaces the intermediate 2 in the preparation process of the modified polyester base fabric in Example 3 with the intermediate 1 in Example 3, and the other steps are the same.

[0011] Comparative Example 3 Compared with Example 3, this comparative example replaces the carbon nanotubes doped in the preparation process of the modified polyester in Example 3 with commercially available Lishuo 20 μm carbon nanotubes in Example 3, and the other steps are the same.

[0012] Comparative Example 4 Compared with Example 3, this comparative example is different in that the wrapped carbon nanotubes in the preparation process of the modified polyester in Example 3 are replaced by doped carbon nanotubes in Example 3, and the other steps are the same.

[0013] Take the antistatic chenille mats prepared in Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4, refer to GB / T 18044-2008, cut 2000mm×1000mm samples, and ensure that the number of chenille piles in each sample is the same, and measure the human walking static voltage by walking test at a temperature of 23°C and a relative humidity of 25% to evaluate the antistatic performance, refer to FZ / T 73023-2006, cut the antistatic chenille mat into samples of 2.5cm×2.5cm in size, and ensure that the number of chenille piles in each sample is the same, and use the oscillation method to measure its antibacterial properties. The test bacteria are Gram-positive bacteria, Staphylococcus aureus and Gram-negative bacteria Escherichia coli. Wash the sample 50 times under the same conditions, and measure its human walking static voltage and antibacterial rate again. Record the human walking static voltage and antibacterial rate after washing, and calculate the antistatic performance residual rate and antibacterial performance residual rate. The antistatic performance residual rate is calculated by dividing the walking static voltage after washing by the walking static voltage before washing, and the antibacterial performance residual rate is calculated by dividing the antibacterial rate after washing by the antibacterial rate before washing, so as to evaluate its long-term performance. The test results are as follows: Test items Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Walking static voltage (kV) 1.14 1.12 1.09 1.17 1.46 1.10 1.21 Antibacterial rate against Gram-positive bacteria (%) 93.38 93.43 93.82 91.36 88.31 84.51 92.07 Antibacterial rate against Staphylococcus aureus (%) 93.74 93.89 94.17 91.68 88.62 84.72 92.20 Antibacterial rate against Gram-negative bacteria Escherichia coli (%) 93.65 93.71 94.06 91.57 88.43 84.67 92.15 Antistatic performance residual rate (%) 98.42 98.57 98.79 84.72 97.45 98.52 94.52 Antibacterial performance residual rate (%) 94.32 94.41 94.73 78.12 93.69 94.59 92.18 It can be seen from the test results in the table shown that when Example 1, Example 2 and Example 3 are compared with Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4, Comparative Example 1 replaces the grafted polyester base fabric in the preparation process of the modified polyester base fabric in Example 3 with a commercially available polyester base fabric, and the water washing resistance is significantly reduced, indicating that the unsaturated groups grafted on the surface of the polyester base fabric and then post-treated can improve its water washing resistance. Comparative Example 2 replaces the intermediate 2 in the preparation process of the modified polyester base fabric in Example 3 with the intermediate 1 in Example 3. Due to the lack of amphoteric groups, its antistatic and antibacterial properties are significantly reduced, indicating that the amphoteric groups can improve its antistatic properties. Energy and antibacterial properties, comparative example 3 replaces the doped carbon nanotubes in the preparation process of the modified polyester in Example 3 with the commercially available carbon nanotubes in Example 3, and its antibacterial properties are significantly reduced due to the lack of silver doping, indicating that silver doping can improve its antibacterial properties, comparative example 4 replaces the wrapped carbon nanotubes in the preparation process of the modified polyester in Example 3 with the doped carbon nanotubes in Example 3, and its antistatic properties, antibacterial properties and water washing resistance all show a certain decline, indicating that the wrapping modification of the doped carbon nanotubes can effectively improve the dispersion of the carbon nanotubes in the polyester and connect the polyester with the carbon nanotubes, thereby improving its antistatic properties, antibacterial properties and water washing resistance.

[0014] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0015] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A production process for an antistatic chenille mat, characterized in that: The modified polyester is prepared by the following steps: Step S1: adding modified polyester to a melt spinning machine, melt spinning to obtain modified polyester filaments, passing through a chenille spinning machine, using two polyester filaments as core yarns, three polyester filaments and two modified polyester filaments as decorative yarns, the polyester filaments and the modified polyester filaments are arranged alternately, and the decorative yarns are sandwiched between the two core yarns and twisted in a spiral shape to obtain modified chenille yarn; Step S2: feeding the modified chenille yarn and the modified polyester base fabric into a tufting loom, and then dyeing, finishing, repairing, and backing to obtain a chenille waterproof floor mat.

2. The production process of an antistatic chenille mat according to claim 1, characterized in that: The modified polyester base fabric is prepared by the following steps: Step A1: Mix a polyester base fabric and a sodium hydroxide aqueous solution, add a hexadecyl trimethyl ammonium bromide solution at a temperature of 80-90° C., soak and react for 1-1.5 hours, and dry to obtain an activated polyester base fabric; mix the activated polyester base fabric, methacrylic anhydride and deionized water, adjust the pH value to 7.5, and soak and react for 24 hours at a temperature of 5° C. to obtain a grafted polyester base fabric; Step A2: methacrylic acid, p-toluenesulfonic acid and trimethyl-1,3-propylenediamine are mixed, and the mixture is reacted for 3-4 hours under nitrogen protection, at a stirring rate of 240-300 rpm and a temperature of 100° C. to obtain intermediate 1; intermediate 1, sodium 3-chloro-2-hydroxypropanesulfonate and anhydrous ethanol are mixed, the pH is adjusted to 7.5, and the mixture is reacted for 6-8 hours under a stirring rate of 240-300 rpm and a temperature of 80° C. to obtain intermediate 2; Step A3: Mix the intermediate 2, methacrylate and deionized water, immerse the grafted polyester base fabric, add 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone, and soak and react for 15-20 minutes under nitrogen protection and 365nm ultraviolet irradiation at room temperature to obtain a modified polyester base fabric.

3. The production process of an antistatic chenille mat according to claim 2, characterized in that: In step A1, the mass concentration of the sodium hydroxide aqueous solution is 1 g / L, the hexadecyltrimethylammonium bromide solution is 2.5 g / L, the amount ratio of the polyester base fabric, the sodium hydroxide aqueous solution and the hexadecyltrimethylammonium bromide is 10-12 g: 100-120 mL: 40-50 mL, and the amount ratio of the activated polyester base fabric and methacrylic anhydride is 10-12 g: 0.08-0.1 mol.

4. The production process of an antistatic chenille mat according to claim 2, characterized in that: In step A2, the ratio of methacrylic acid, p-toluenesulfonic acid and trimethyl-1,3-propylenediamine is 0.1-0.12 mol: 0.5 g: 0.1-0.12 mol, and the ratio of intermediate 1 and sodium 3-chloro-2-hydroxypropanesulfonate is 0.1-0.12 mol: 0.12-0.14 mol.

5. The production process of the antistatic chenille floor mat according to claim 2, characterized in that: In step A3, the amount ratio of intermediate 2, methacrylate, deionized water and 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone is 0.1 mol: 0.1-0.12 mol: 150-200 mL: 2-3 g.

6. The production process of the antistatic chenille floor mat according to claim 1, characterized in that: The modified polyester is prepared by the following steps: Step B1: Mix carbon nanotubes, nitric acid solution and sulfuric acid solution, and react for 1 hour at a stirring rate of 200-240rpm and a temperature of 110°C to obtain activated carbon nanotubes; mix sodium alginate, silver nitrate solution and deionized water, and stir and add glucose solution at a stirring rate of 200-240rpm and a temperature of 80°C, and react for 2 hours; then add activated carbon nanotubes and continue to react for 4-6 hours to obtain doped carbon nanotubes; Step B2: Mix the doped carbon nanotubes, methanol and deionized water, stir and add 3-(methacryloyloxy)propyltrimethoxysilane at a stirring rate of 300-360 rpm and a temperature of 50°C, adjust the pH to 3.5, and react for 4-6 hours to obtain grafted carbon nanotubes. Mix lactide and N,N-dimethylformamide, stir and add grafted carbon nanotubes and stannous octoate at a stirring rate of 300-360 rpm and a temperature of 120°C, and react for 6-8 hours to obtain wrapped carbon nanotubes; Step B3: Mix the wrapped carbon nanotubes, dimethyl terephthalate and ethylene glycol, stir and add n-butyl titanate at a stirring rate of 200-240 rpm and a temperature of 200°C, react for 1-2 hours, then heat it to 250°C and control the vacuum degree to -0.099 MPa, react for 6 hours to obtain modified polyester.

7. The production process of the antistatic chenille floor mat according to claim 6, characterized in that: In step B1: the mass fraction of nitric acid solution is 65%, the mass fraction of sulfuric acid solution is 95%, the amount ratio of carbon nanotubes, nitric acid solution and sulfuric acid solution is 0.5-1g:10-12mL:30-36mL, the molar concentration of silver nitrate solution is 0.1mol / L, the mass fraction of glucose solution is 5%, and the amount ratio of sodium alginate, silver nitrate solution, glucose solution and activated carbon nanotubes is 100mL:10-12mL:45-50mL:0.2g.

8. The production process of the antistatic chenille floor mat according to claim 6, characterized in that: In step B2: the ratio of doped carbon nanotubes to 3-(methacryloyloxy)propyltrimethoxysilane is 1.8-2.2 g: 0.1-0.12 mol, and the ratio of lactide, grafted carbon nanotubes and stannous octoate is 0.005-0.008 mol: 1.8-2.2 g: 0.1 g.

9. The production process of the antistatic chenille floor mat according to claim 6, characterized in that: In step B3: the amount ratio of wrapped carbon nanotubes, dimethyl terephthalate, ethylene glycol and n-butyl titanate is 4-5 g: 0.5-0.55 mol: 0.8-1 mol: 0.2-0.25 g.

10. An antistatic chenille floor mat, characterized in that: Prepared according to any one of the production processes described in claims 1-9.